Green Synthesis of Cupric Oxide Nanoparticles Using Water Extract of Murrya koenigi and its Photocatalytic Activity - Anandhavalli, N.; Mol, Bency; Manikandan, S.; Anusha, N.; Ponnusami, V.; Rajan, K.S. (Asian Journal of Chemistry, 2015)
Green synthesis of cupric oxide nanoparticles has been carried out from copper sulphate pentahydrate using the water extract of Murrya koenigi. The components present in the water extract react with copper sulphate pentahydrate to form an intermediate, which upon calcination at 300 ºC resulted in the formation of cupric oxide. The synthesized nanoparticles were spherical in shape and about 33-40 nm in size. X-Ray diffraction pattern confirmed the crystalline nature of cupric oxide. The green-synthesized cupric oxide nanoparticles possess excellent photocatalytic activity with about 80 % dye degradation in 10 min from initial concentration of 50 ppm.